Analisa Terhadap Ketentuan Cuti Melahirkan dalam Pasal 82 Ayat (1) UU No. 23 Tahun 2003 Tentang Ketenagakerjaan dan Kaitannya dengan Hak Bayi atas ASI Ekslusif - Tisa Windayani (Jurnal Paradigma Hukum Pembangunan, 2016)
The role and number of women workers is considerably significant in Indonesia. It is important then, to assure that their rights are well protected. One of the rights is the right of maternity leave. Article 82 Par (1) Law Number 23/2003 on Labour as the only provision that regulates this right in Indonesia, in which the time scheme on when do pregnant workersstart their maternity leave has been arranged, is deemed to be a potential determinant in causing a failure of exclusive breastfeeding. This is because the unclear interpretation generated from the formulation of the article. This paper would present an analysis on Article 82 Par (1) as well as academically-based suggestion on how should the article is interpretedin the light of the right of the infants to be exclusively breastfed.